Fusobacterium nucleatum induces chemoresistance in colorectal cancer by inhibiting pyroptosis via the Hippo pathway - Ni Wang; Lu Zhang; Xiao-Xu Leng; Yi-Le Xie; Zi-Ran Kang; Li-Cong Zhao; Lin-Hong Song; Cheng-Bei Zhou; Jing-Yuan Fang (Gut Microbes, 2024)
ABSTRACTChemotherapy resistance is one of the main reasons for the poor prognosis of colorectal cancer (CRC). Moreover, dysbiosis of gut bacteria was found to be a specific environmental risk factor. In this study, enrichment of F. nucleatum was elucidated to be significantly associated with CRC recurrence after chemotherapy. Functional experiments showed that F. nucleatum could inhibit pyroptosis induced by chemotherapy drugs, thereby inducing chemoresistance. Furthermore, mechanistic investigation demonstrated that F. nucleatum could regulate the Hippo pathway and promote the expression of BCL2, thereby inhibiting the Caspase-3/GSDME pyroptosis-related pathway induced by chemotherapy drugs and mediating CRC cell chemoresistance. Taken together, these results validated the significant roles of F. nucleatum in CRC chemoresistance, which provided an innovative theoretical basis for the clinical diagnosis and therapy of CRC.